(untitled) (Revista Espacio Regional, 2021)
This article seeks to translate a little bit of the reality of women linked to agro-ecology in one of the regions of Paraná, in southern Brazil, as well as articulate the particularity of their experiences with the training history of thinking and doing agroecology in order to pinpoint specific demands arising from the experiences of women and the need to consider in different ways gender relations in this journey to build a new fairer way of organizing life. Discuss all the ramifications that agroecological proposal has undergoes to consider the diversity on a broad and unrestricted way, this way we understand that women play a central role in the production of active resistance against the normative standards that surround multiple forms